Le consentement en matière d'agression sexuelle: peut-on sortir du labyrinthe sans le fil d'Ariane? - Manganas, Antoine (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1988)
The author attempts to demonstrate the difficulty of applying the new test provided by s. 244(4) of the Criminal Code and concerning the sincerity of the accused's belief in a case of sexual aggression. Even if the judges of the Supreme Court of Canada, in two recent decisions (Bulmer and Robertson), reaffirmed the principle of Pappajohn that an honest and sincere mistake of fact to the existence of the victim's consent can constitute a defence to a criminal charge, we must give an explanation why the legislator changed the law by introducing this partly subjective and partly objective test. The author think that this new test creates much confusion ; it will be very difficult for judges to explain it adequately to the jury and for jury members to understand its real meaning. In conclusion, the author believes that once again the legislator created an ambiguous situation because he did not dare to impose a clearly objective test.